Singapore tertiary students: the way they select their main and subsidiary bank. - Ow, Kevin Yong Keng. (2008)
Firstly, the study will determine the extent of multiple banking among the tertiary student population. Secondly, the study will ascertain whether there are any significant differences in the bank selection criteria of a main bank user versus a single bank user. Finally, the study will determine if there are any significant differences in the bank selection criteria of a multiple banking customer upon comparing main bank selection with subsidiary bank selection.